THE ROLE OF AN ADVOCATE IN PROTECTING THE LEGAL INTERESTS OF A CLIENT - Ronaldo; Ahmad Irzal Fardiansyah; Muhtadi (Progressive Law Review, 2025)
The legal profession of advocates holds an important role within Indonesia’s legal system. As legal enforcers tasked with providing legal assistance and protecting the legal interests of their clients, advocates serve not only as defenders in judicial proceedings but also as guardians of balance in law enforcement and protectors of human rights. This study aims to analyze the role of advocates in law enforcement, particularly in safeguarding clients’ legal interests based on Law Number 18 of 2003 concerning Advocates. The research employs a normative legal method with an analytical and statute approach through literature studies of legislation, books, and relevant journals. The results indicate that advocates play a strategic role in ensuring justice, legal certainty, and the protection of clients’ rights at every stage of the legal process—criminal, civil, and administrative. Advocates are also obliged to provide free legal aid to underprivileged communities. In carrying out their profession, advocates are required to uphold the code of ethics, integrity, and independence in order to maintain the dignity of the profession and uphold the rule of law. Thus, advocates serve as a key pillar in realizing a fair, transparent, and socially just judicial system for all citizens.